Analysis and the methods of reducing vehicle thermal loads - Chan, Benjamin Jia Jun. (2013)
This report serves as a guide to understanding and analyzing the different methods to reduce the vehicle thermal loads. The project started out with 3 objectives being defined namely to obtained the thermal loads and power requirement, to analyze the different materials used for the car and the vehicle geometry and design which can ultimately reduce this thermal heat load and finally to optimize the vehicle thermal design using all these findings. The base model used is a Nissan Leaf and as geometry was a variable in this experiment, the author generated various 3D CAD car models with varying geometry from 0° to 40° with the aid of Solidworks. The control for this experiment would be the default car model with geometry of -25°. Thermal simulations were carried out on the volume in the cabin interior and the various components via THESEUS-FE software. There was a total of 5 experiments that were be carried out to see find the optimal design that can reduce the thermal load in the vehicle in terms of geometry and materials.